A study of Sudden Enhancement of Atmospherics on 27 kc/s band (MAUSAM, 1962)
The paper reports a study of Sudden Enhancement of Atmospheric (S.E.A.) on 27 kc/s at a station in low latitudes carried out during 1958-59, which is thought to be of importance for the world-morphology of S.E.A.  It is found here that S.E.A. shows maximum association with magnetic chrochet.  The chances of occurrence of S.E.A. are practically the same for most of the day hours.  The rise-time and decay-time of S.E.A, have average ratio of about 1:4, with a total duration of about 40 minutes.  The rise-times cluster around tow distinct values of 5 minutes and 15 minutes.  The total duration of S.E.A. is seen to increase with its amplitude, whereas the rise-time does not increase with amplitude.  Further it is observed that the S.E.A.s with rise-times greater than about 13 minutes are more in the forenoon than in the afternoon.